2016
DOI: 10.1039/c6ay00098c
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric determination of diazepam using a bismuth modified pencil graphite electrode

Abstract: CVs of diazepam at the different PGEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
11
1
Order By: Relevance
“…Also, the performance of this PPGE is comparable to that of pencil graphite electrodes modified by other materials. 34, [38][39][40] Besides, because of nonuse of expensive materials for electrode modification and easy-touse application of this sensor, this sensor is superior to other modified pencil graphite electrodes.…”
Section: Potentiodynamic Methodsmentioning
confidence: 99%
“…Also, the performance of this PPGE is comparable to that of pencil graphite electrodes modified by other materials. 34, [38][39][40] Besides, because of nonuse of expensive materials for electrode modification and easy-touse application of this sensor, this sensor is superior to other modified pencil graphite electrodes.…”
Section: Potentiodynamic Methodsmentioning
confidence: 99%
“…510 Bi compounds have been used to modify different carbonaceous electrode materials, such as carbon pastes, 511 graphite-epoxy composites, 512 borondoped diamond, 513 carbon films, 514 glassy carbon, 431 screenprinted carbon inks, 515 or pencil graphite. 516 Bi has also been deposited in combination with polymers, 517,518 and on metallic electrodes, such as Au, Cu, or Pb. 449 Studies have shown that the incorporation of Bi NPs onto an electrode surface is more attractive compared to pre-plating the BiFEs on the electrode.…”
Section: Bi Nanocrystals and Bi Film Electrodes (Bifes) For Biosensingmentioning
confidence: 99%
“…Where, I pa is Anodic peak current, n is the number of electrons transferred, A 0 is surface area of the electrode (cm 2 ), D 0 is diffusion coefficient, C is concentration of Fe(CN) 6 3À/4À and u is the scan rate, R is molar gas constant (8.314 JK À1 mol À1 ) and F is Faraday's constant (96480 C mol À1 ). For 1.0 mM K 3 Fe(CN) 6 in 0.1 M KCl at Temperature, T = 298 K, n = 1 and D 0 = 7.6 3 10 À6 cm 2 s À1 . The surface area is calculated from the slope obtained from plot of I pa versus u 1/2 and by putting the values in above equation with scan rate 50 mV s À1 .…”
Section: Cyclic Voltammetric Characterization Of Electrodementioning
confidence: 99%